Solar photovoltaic system fed water pumping system using BLDC motor with single input and multiple output converter - Chaitanya, Kommera; Pradhan, Arjyadhara; Panda, Babita (Institute of Advanced Engineering and Science, 2025)
In recent times energy based on renewable energy sources is a good long-term alternative compared with traditional fossil fuel energy sources solar photovoltaic model-based irrigation water pump systems have gained more popularity. The one-input and multi-output converters are focused on BLDC motor drive-based solar photovoltaic with water pump. To model one input and multiple output converter components are connected viz it achieves tracking purpose and BLDC drive soft starting. The one-input and multiple-output converter exhibits the features of all converters and remarkably appears with the converter in the application of solar photovoltaic systems. It describes performance under varying environmental and inspects the BLDC motor effective with the suggested single input and multiple output converter for solar photovoltaic with a water pump with 95% efficacy and the price is USD 0.6/W. Test results have confirmed the BLDC motor suitability for solar photovoltaic with water pump employing MATLAB Toolbox followed by the test result verification. It is simply developed for rural areas because it is low cost, simple, and low maintenance.